Context of Reception and School Violence: Exploring the Nexus of Immigration, Race/Ethnicity, Place, and School Crime. Issue 3 (July 2021) - Peguero, Anthony A.; Irizarry, Yasmiyn; Iwama, Janice A.; Dunning-Lozano, Jessica L.; Sung Hong, Jun; King, Sanna
Of course, ensuring safe environments in the U.S. educational system is paramount. It is also evident, however, inequalities associated with immigration, race/ethnicity, and situational context can impede school safety pursuits. Although prior research has revealed a pattern between "downward" assimilation and increased experiences with student-level violence and disorder for the children of racial/ethnic immigrants (i.e., first- and second-generation), investigations about school-level rates of violence and disorder associated with the context of reception remain uncertain. Our study seeks to contribute to the research about immigration, racial/ethnic inequality, education, and violence by examining the associations between context, school violence, and crime, and the schooling of children of immigrants by drawing on a context of reception conceptual framework to address three research questions. First, is there an association between an increasing proportion of children of immigrants and school crimes (i.e., violence, property damage, and substance use)? Second, are there differences linked to the context of reception (i.e., urban, suburban, town, and rural) in the association between the increasing proportion of children of immigrants and school crime? Third, are there racial/ethnic differences in the association between the increasing proportion of children of immigrants and school crimes in distinct contexts? Findings indicate that the children of racial/ethnic minority immigrants have significantly distinct associations with rates of school violence and crime across all contexts; however, there are important and distinctive nuances that are presented and examined.